超大模数齿轮的参数化建模及接触分析 - 马宝; 唐文献; 章子玲; 张爽爽 (Jixie chuandong)
Theoretical calculation of the strength for suppermodulus pinion is lacking.For involute cylindrical pinion,which was designed for rack and pinion jacking systems in wind power installation vessel,by analyzing modification theory,is accurately built parametric model of rack and pinion of which based on Pro/E.On the basis of analysis of actual working conditions of jacking systems,law of contact stress and bending stress in an engagement cycle are studied.The results show tooth surface spears uneven contact stress and obvious edge effect; differences between tooth root tensile stress and press stress;the largest contact stress appear on down boundary point of single tooth and largest bending appear on up boundary point of single tooth.